The DDT‐induced decline influenced genetic diversity in naturally recovered Peregrine falcons (Falco peregrinus) nesting within the Alaska Arctic and eastern interior. (19th July 2022) - Sonsthagen, Sarah A.; Swem, Ted; Ambrose, Skip; Flamme, Melanie J.; White, Clayton M.; Sage, George K.; Talbot, Sandra L.
Abstract : We assessed the influence of the severe mid‐20 th century population decline on genetic diversity in non‐augmented Peregrine Falcon Falco peregrinus populations nesting within the Alaska Arctic and eastern Interior. Microsatellite and mitochondrial DNA (mtDNA) data were analysed for Peregrine Falcons sampled from three periods: pre‐decline, decline and post‐decline. The influence of the decline on genetic diversity differed between the two locales. The Alaska Arctic was characterized by shifts in mtDNA haplotype frequencies, increased inbreeding coefficient, reduction in effective population size and increase in private haplotypes, and a signature of post‐decline population growth was detected; by contrast, the eastern Interior showed a reduction in haplotype diversity and no differences in allelic or haplotypic frequencies between pre‐ and post‐decline periods, though pre‐decline birds clustered away from the other two periods and allelic frequency differences were observed between decline and post‐decline periods. Patterns in genetic diversity suggest populations recovered through recruitment from within and immigration.